2009
DOI: 10.1007/bf03395671
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Validity of the Implicit Relational Assessment Procedure and the Implicit Association Test: Measuring Attitudes Toward Dublin and Country Life in Ireland

Abstract: The current study aimed to test the validity of the Implicit Relational Assessment Procedure (IRAP), as compared to the Implicit Association Test (IAT), by assessing the attitudes of Dublin dwellers and rural dwellers towardThe currently most popular and well-researched measure of so-called implicit attitudes is the Implicit Association Test, or IAT (Greenwald, McGhee, & Schwartz, 1998). The core assumption underpinning the method is that individuals should respond quickly when asked to emit a similar response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 15 publications
(17 reference statements)
1
25
0
Order By: Relevance
“…As predicted, response latencies were faster for consistent than for inconsistent trials (e.g., participants responded more quickly to Pleasant-Love-Similar than to Pleasant-Love-Opposite). These results have since been replicated across a small number of other studies (e.g., Barnes-Holmes, Murphy, BarnesHolmes, & Stewart, 2010;Barnes-Holmes, Waldron, Barnes-Holmes, & Stewart, 2009;Cullen, Barnes-Holmes, Barnes-Holmes, & Stewart, 2009;Dawson, Barnes-Holmes, Gresswell, Hart & Gore, 2009;McKenna et al, 2007;Power, Barnes-Holmes, Barnes-Holmes, & Stewart, 2009;Roddy, Stewart, & BarnesHolmes, in press;Vahey, Barnes-Holmes, Barnes-Holmes, & Stewart, 2009). Nevertheless, research on the IRAP as an implicit measure is very limited, and further empirical study is required before its reliability and validity can be determined.…”
mentioning
confidence: 58%
“…As predicted, response latencies were faster for consistent than for inconsistent trials (e.g., participants responded more quickly to Pleasant-Love-Similar than to Pleasant-Love-Opposite). These results have since been replicated across a small number of other studies (e.g., Barnes-Holmes, Murphy, BarnesHolmes, & Stewart, 2010;Barnes-Holmes, Waldron, Barnes-Holmes, & Stewart, 2009;Cullen, Barnes-Holmes, Barnes-Holmes, & Stewart, 2009;Dawson, Barnes-Holmes, Gresswell, Hart & Gore, 2009;McKenna et al, 2007;Power, Barnes-Holmes, Barnes-Holmes, & Stewart, 2009;Roddy, Stewart, & BarnesHolmes, in press;Vahey, Barnes-Holmes, Barnes-Holmes, & Stewart, 2009). Nevertheless, research on the IRAP as an implicit measure is very limited, and further empirical study is required before its reliability and validity can be determined.…”
mentioning
confidence: 58%
“…This is in line with (1) previous SE IRAP effects (e.g., [40] and [41]) and (2) findings for the 'universality' of self-positive implicit biases (e.g., [37]). An odd-even split-half procedure (applying the Spearman-Brown formula) was used to assess the reliability of the IRAP [42]. Split-half reliability was 0.85, which is comparable to other IRAP measures [43] and other implicit SE measures [44] and suggested that the IRAPSE reliably detected unintentional selfevaluations (in this case, implicit SE).…”
Section: Preliminary Analysesmentioning
confidence: 74%
“…The primary datum was response latency, defined as the time in milliseconds that elapsed between the onset of a trial and a correct response emitted by a participant. To control for individual variations in speed of responding that may act as a possible confound when analyzing between-group differences, the response latency data for each participant were transformed into D IRAP scores (Barnes-Holmes, Murtagh, et al, in press;Barnes-Holmes et al, 2009;Cullen & Barnes-Holmes, 2008;Vahey et al, 2009) using an adaptation of the Greenwald, Nosek, and Banaji (2003) …”
Section: Resultsmentioning
confidence: 99%